Rancang Bangun Aplikasi Computer Based Test (CBT) Untuk Membantu Siswa Dalam Melaksanakan Ujian - Rahayu, Sri Lestari; Sari, Rita Novita; Hayati, Ratna Sri; Surbakti, Muhammad Aditya (LPPM Universitas Potensi Utama, 2024)
The rapid development of information technology has driven its utilization in various activities, including the education sector. One of its applications is the Computer-Based Test (CBT) system, which replaces conventional paper-based exams. SMK PAB 8 Sampali faces challenges in conducting paper-based exams, such as the risk of grading errors and inefficiency in the process. Therefore, developing a CBT application is a potential solution to improve the quality of exam administration. This application allows students to easily complete exam questions using internet-connected devices, eliminating the need for additional writing tools. Teachers also benefit from a more efficient grading process and structured evaluation reports. This research aims to design and develop a CBT application to support exam administration at SMK PAB 8 Sampali, with the hope of providing significant benefits for students, teachers, and other users. Additionally, training provided by the researchers aims to enhance students' knowledge of the Computer-Based Test (CBT) application to assist them in taking exams.